"I prepared my own carrots". The effect of participation in an out-of-home cooking session on Dutch 4–6-year-old children's vegetable consumption. (December 2020) - Zeinstra, Gertrude G.; Vrijhof, Milou; Kremer, Stefanie
Highlights: The effect of an interactive cooking session was experimentally investigated. One vegetable preparation session did not increase children's vegetable intake. A small positive effect on involvement in food-related activities at home was found. Based on children's vegetable eating patterns, four different clusters were identified. Abstract: Involvement in vegetable preparation is thought to be an effective strategy to increase children's vegetable intake, but the evidence from experimental studies is scarce. A between-subject experiment was executed in a restaurant setting to investigate the effect of participation in vegetable preparation on 4–6-year-old children's vegetable intake. After a baseline evening meal, intervention children (N = 50) participated in a vegetable preparation session together with an enthusiastic chef. Control children (N = 51) participated in small groups in a book-reading activity. Subsequently, they ate an evening meal. Follow-up sessions at one month and three months were included to assess possible longer-term effects. Vegetable intake was the main outcome. Secondary outcomes were vegetable choice and involvement in food-related activities at home. For all four sessions, children's vegetable intake ranged between 50 and 60 g in both conditions (p > 0.05). Participation in carrot preparation did not increase children's vegetable intake. Involvement in food-related activities at home remained stable in the intervention group, whereas it decreased slightly in the control group (p = 0.01). A cluster analysis identified four distinct vegetable eating patterns over time, suggesting that there are different segments of children. To conclude, participating once in an out-of-home vegetable preparation session with an enthusiastic chef did not influence children's intake of a familiar vegetable, but it may support their general involvement in food-related activities at home.